Creative Economy Development in PAK Theology for the Achievement of SDGS Goals in the STT Environment - Stefanus , Tonny Andrian; Simanjuntak, Joksan; Saerang, Lodewyik; Pentury, Thomas; Rajagukguk, Wilson (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
The development of creative economy in Christian Religious Education Theology (PAK) is a strategic approach for Theological Colleges (STT) to achieve local economic prosperity in the midst of a digital revolution towards the achievement of SDGs. Creative economy is a global strategy, including in Indonesia, to create economic added value. The integration of the creative economy in PAK Theology encourages students to improve their creative economic skills in areas such as spiritual design, digital content production, learning media, service entrepreneurship, and social innovation based on faith. This integration enriches the PAK theological learning process but also increases student participation in church and community service, an integral part of the cultural mandate.Research findings indicate that the development of the creative economy has a significant impact on the achievement of various Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), SDG 8 (Economic Growth and Decent Work), SDG 9 (Innovation and Infrastructure), and SDG 11 (Sustainable Communities). Therefore, the integration of creative economy development in PAK Theology not only increases the academic relevance of STT, but also serves as a tangible contribution to sustainable development in the era of Industry 5.0. It is hoped that STT graduates will become independent, innovative, adaptive, and visionary graduates who can think far ahead and play a role as agents of reform in the digital, social, and community welfare fields.